2021
DOI: 10.3390/vaccines9101117
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and Children’s Complete Vaccination in the Democratic Republic of the Congo: A Cross-Sectional Analysis

Abstract: (1) Background: The empowerment of women contributes to better child health and wellness. This study aimed to examine the association between women’s empowerment and complete vaccination of children, as recommended in the National Expanded Program on Immunization (EPI) in the Democratic Republic of the Congo (DRC). (2) Methods: In this cross-sectional study, a principal component analysis (PCA) was conducted on data from the Multiple-Indicator Cluster Survey 6 (MICS-6) to determine the dimensions of women’s em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…It was evident from this study that the odds of vaccination dropout in children from women with low levels of empowerment was 1.63 higher compared to children from women with high levels of empowerment. This aligns with studies conducted in Mozambique and the Democratic Republic of the Congo ( 51 , 53 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was evident from this study that the odds of vaccination dropout in children from women with low levels of empowerment was 1.63 higher compared to children from women with high levels of empowerment. This aligns with studies conducted in Mozambique and the Democratic Republic of the Congo ( 51 , 53 ).…”
Section: Discussionsupporting
confidence: 89%
“…Our finding is consistent with studies conducted in Nigeria, Benin, and the Democratic Republic of the Congo. Using a nationally representative data, Ataguba et al stated that existing immunization coverage disparities disproportionately benefited the rich ( 37 , 38 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 systematic review found that greater household and healthcare decision-making power by women was associated with higher odds of complete childhood immunization [19]. Subsequent analyses have found similar associations in Kenya [20], Ethiopia [21], and the Democratic Republic of the Congo [22].…”
Section: Introductionmentioning
confidence: 98%
“…Women empowerment and higher socioeconomic standing have a vital role in the promotion of complete immunization of children, as reflected by the study done by Lu Xinran, et al in Congo 15 . In our study, 45.6 % of cases and 64.5% of controls represented empowered mothers for the childhood vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…For sample size calculation, we took 95% twosided significance level (1-alpha), and 90% power. 55% (Educated mothers with incomplete immunization) in cases and 68.6% 15 in control (un-educated mothers with incomplete immunization). A total of 434 patients were enrolled in study; 217 in the case and 217 in the control group.…”
Section: Patients and Methodmentioning
confidence: 97%